STRATEGI PEMBENTUKAN KARAKTER KEPEMIMPINAN SANTRI - Prabowo, Aji Bayu; Muntaqo, Lutfan; Linnaja, Ngatoillah (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2024)
This article aims to analyze the strategy for forming the leadership character of students in the Ma'arif Council organization of the Tanbihul Ghofiliin Islamic Boarding School, Banjarnegara. This research uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews, observation, and documentation. Data validity was verified through triangulation of sources and methods, followed by thematic analysis. The findings indicate that the implementation of leadership character building strategies is carried out through two main approaches: formal education and non-formal activities. Formal education, through religious classes, plays a role in providing a foundation of knowledge about Islamic leadership values. Subjects such as Fiqh (Islamic jurisprudence), Aqidah (creed), and Sirah Nabawiyah (the Prophetic tradition) help students understand leadership concepts in depth. Non-formal activities, such as involvement in organizations, provide students with opportunities to practice the leadership values they have learned. The role model approach also plays a crucial role in the implementation of leadership character building. This process has implications for individual students, their social environment, and the educational system at Islamic boarding schools. In terms of personal development, students involved in leadership programs demonstrate improvements in responsibility, independence, and self-confidence. They learn to become proactive individuals and capable of leading groups, both within the Islamic boarding school environment and in the community after graduation.